Application of Treffinger Learning Model Combined With Audio Visual Media To Improve Basic Chemistry Learning Outcomes STKIP PI Makassar Students - Haris Munandar; Muhammad Fath Azzajjad; Dewi Satria Ahmar (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The research is Classroom Action Research, which aims to improve basic chemistry student learning outcomes with the application of Treffinger's learning model with the help of audio visual media on colloidal system materials. Data collection techniques can be done with an observation sheet of student learning activities and evaluation at the end of each cycle. The collected data is analyzed using descriptive statistical analysis. The results showed that the application of Active Knowledge Sharing strategy with Buzz Group method can improve basic chemistry learning outcomes in STKIP PI Makassar students which is characterized by an increase in the average learning outcome of cycle I students by 63.33 and cycle II by 72.67 and an increase in the completion of learning outcomes in cycle I which is 9 people or 22.5% and cycle II 35 people or 87.5%.